The iconic American Western in film and literature - Zaidi, Ali Shehzad (Acta neophilologica, 2017)
This essay examines representative stories of the American Western genre in both film and literature in light of various literary influences, including The Bible and classical epics such as Gilgamesh, The Iliad, and The Odyssey. These stories relate the dynamic tensions of characters caught between righteous and unrighteous anger, between home and longing for the road, and between the imperative to survive and the impulse to sacrifice oneself for others.
Keywords: American literature; ameriška književnost; Ep o Gilgamešu; filmski žanri; Iliada; Leonard, Elmore: Hombre; Schaefer, Jack: Shane; Točno opoldne; western